PENGARUH PADAT PENEBARAN TERHADAP PERTUMBUHAN IKAN KERAPU SUNU (Plectropomus leopardus) YANG DIPELIHARA DALAM KARAMBA JARING APUNG - Sunirco, Sunirco; Serdiati, Novalina; Madinawati, Madinawati (AgriSains, 2012)
This study aims to determine the effect of stocking density on growth of Trout Grouper (Plectropomus leopardus) were cultured in the floating net cage. The study was conducted in Tolobundu Bay, Popidolon Village, Liang District, the residence of Banggai Islands, Central Sulawesi Province, during period of June to August 2011. Experimental organisms used were Trout Grouper (Plectropomus leopardus) with initial body weight of 200 g/head. Twelve 1 m x 1 m x 1m floating net cages with mesh sizes 1 inch were used for this experiment. Feeds given were trashed raw fishes amounted to 4-5% of the grouper biomass, fed three times daily. Experimental design used was completely randomized design (CRD) with 3 treatments, namely stocking densities of 15; 20 and 30 heads/m3, respectively, and with four replications. The results showed that the stocking density have a highly significant effect on the growth of Trout Grouper (Plectropomus leopardus), where the highest growth was performed by those cultured with stocking density of 15 heads/m3.Key words : stocking density, growth, Trout Grouper.